Detection of Salmonella enterica serotype Typhimurium DT104 in chickens meat / Nadia Jasmi - Jasmi, Nadia (2007)
An increase in the prevalence of Salmonella enterica serotype Typhimurium DTI04 has been reported worldwide. Salmonella enterica serotype Typhimurium is recognized as a significant of human pathogen. These organisms are often resistant to five or more antimicrobial agents namely ampicillin (A), chloramphenicol (C), streptomycin (S), sulfonamides (Su), and tetracycline (T) -the characteristic resistance (R) type ACSSuT. In addition, reporting of resistance to fluroquinolones or extended-spectrum cephalosporins is also increasing annually. This study examined the detection of this Salmonella serogroup B isolates in chicken meat as well as determined the antibiotic resistance pattern. A total of 20 chicken meats were obtained from wet market in the vicinity of Petaling Jaya. Of these, 4 (20%) of the isolates were identified as Salmonella spp. isolates. These isolates were tested by a conventional culture method and resistance patterns to four antibiotics namely ampicillin, chloramphenicol, tetracycline and ciprofloxacin for the identification of Salmonella typhimurium DTI04. Based on the zone of inhibition, 100% of Salmonella isolates were found resistance to ampicillin and tetracycline and 50% of the isolation were shown resistance to chloramphenicol and ciprofloxacin.